Design and realization of low-cost solenoid valve remotely controlled, application in irrigation network - Abdelhamid Benbatouche; Boufeldja Kadri (Bulletin of Electrical Engineering and Informatics, 2022)
The remote and automated irrigation system of farmlands can avoid and minimize the waste of water and energy resources. This can be done with the remote-control of the solenoid-valves. A new solenoid-valve was designed and built from a simple valve with a motor and switches. The remote and automated irrigation system can monitor and receive requests via short message service (SMS) or web interface for controlling pump or solenoid-valves connected to the system. After each operation performed by the system, users receive notifications via SMS messages that contain the real-time status of the solenoid-valves controlled or temperature and humidity value. This system was created using Raspberry-Pi as the system control center. It has been connected to several sensors, and raspicam is used to take photo or video capture in real-time after the users’ request, and the global system mobile (GSM) module is a communication interface used to receive requests for controlling the irrigation system or to send notifications to users. A website is also developed for consultation and control of all that it contains in the system remotely. The result of this research aims to build a secure remote and automated irrigation system including low-cost solenoid-valve with Raspberry-Pi based on control and notification via SMS and web-page.